The battle for Congress : consultants, candidates, and voters - Thurber, James A., 1943- (Washington, D.C. : Brookings Institution Press, 2001)
Introduction -- One years and four elections: the 1998 capps campaign for California's twenty-second district Jeff Gill -- Johnson versus Koskoff: the 1998 campaugn for connecticut's suxth District -- High turnout in a Low-Turnout year: Georgia's Second District -- Kansas's Third District: The "pros from Dover" set Up Shop -- Brian Baird's "Ring of fire": The quest for funds and votes in Washington's third district -- Wisconsin's second district: History in the making -- Appendix: case study framework and methodology.
Introduction / James A. Thurber -- One year and four elections : the 1998 Capps campaign for California's 22nd District / Jeff Gill -- Johnson vs. Koskoff : the 1998 campaign for the Connecticut's 6th District / Diana Evans -- High turnout in a low turnout year : Georgia's 2nd District / Charles S. Bullock -- Kansas's 3rd District : the "Pros from Dover" set up shop / Burdett A. Loomis -- Brian Baird's "Ring of fire" : quest for campaign funds and votes in Washington's 3rd District / James A. Thurber and Carolyn Long -- Wisconsin's 2nd District : history in the making / David T. Canon.
Includes bibliographical references and index.
Keywords: United States. -- Congress. -- House -- Elections, 1998 -- Case studies; Political campaigns -- United States -- Case studies; Political consultants -- United States -- Case studies; Política -- Estados Unidos -- Estudio de casos; Campaign management -- United States -- Case studies